Photoresponse of composites of zinc oxide and poly(3-hexythiophene) under selective UV and white-light illumination - Pattamang, Pattaraluck; Jiramitmonkon, Kanpitcha; Piyakulawat, Phimwipha; Asawapirom, Udom; Tantisantisom, Kittitpong; Porntheeraphat, Supanit; Nukeaw, Jiti; Pratontep, Sirapat (My University, 2016)
We investigate charge transport in UV sensing devices based on organic-inorganic semiconductor composites with the metal-semiconductor-metal (MSM) structure. Composite materials of zinc oxide (ZnO) nanoparticles and poly(3-hexylthiophene) (P3HT) were prepared by drop-casting their colloidal mixture in chloroform onto low-cost interdigitated copper electrodes. The current-voltage characteristics of the devices were investigated under both dark and illuminated conditions in the UV–visible range. The highest photoresponse was observed for an optimal P3HT:ZnO ratio of 1:8 w/w in the wavelength range between 310 and 380 nm. The dynamic response was investigated by pulsing a 365 nm UV light with a long period to reveal the response time of 4 s and the recovery time of less than 1 s. The photoresponse of the materials was also investigated for a shorter period of UV pulsing, using a rotating chopper. The response time and recovery time for the short UV pulse were found to be approximately 20 m and 25 m, respectively. The dual response times should stem from the presence of two types of semiconductor materials, namely ZnO with a high electron mobility and P3HT with a moderate hole mobility. To probe the charge generation and transport mechanisms, we further investigate the photoresponse using UV pulsing under background white light of different intensities, and vice versa. The background white light was found to deteriorate the UV photoresponse of the materials. On the other hand, the background UV illumination produced an anomalous photoresponse pattern with the white light pulsing. Understanding the charge transport mechanisms for composite materials is highly important for future applications in low-cost UV sensors and tunable optoelectronic devices.
Keywords: Organic-inorganic composites; Polythiophene; Selective illumination; UV sensors; Zinc oxide